Manajemen Pembelajaran Boarding School - Mus, Sumarlin; Mappincara, Andi (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2019)
The boarding school learning system requires students to stay in one dormitory. Therefore, teachers or educators more easily control the character development of students. Curricular, curricular, extracurricular activities, both in schools, dormitories and the community environment are monitored by the teachers for a full day. The suitability of the boarding system lies in all student activities programmed, arranged and scheduled clearly. This is the basis for researchers to examine how the learning management of schools that apply boarding schools. The research method used to find out the entrepreneurial competencies of principals is by a qualitative approach with principals, teachers, and students. Data collection is done by in-depth interviews. The results of this study concluded that, the implementation of learning at Pesantren Putri Ummul Mukminim had carried out the concept of Fullday school in learning by doing indoor and outdoor learning as a development of the theory gained in the classroom then applied outside the classroom / school.